PENGARUH LIBERALISASI TERHADAP PERDAGANGAN BILATERAL JEPANG DENGAN CINA DAN ASEAN-5 - Sumaryadi, Nurcahyaningtyas S (KINERJA, 2003)
This study provides the possible effects of trade liberalization commitments (WTO and APEC) on the bilateral trade between Japan and the ASEAN-5 countries (Indonesia, Thailand, Phillipines, Malaysia and Singapore) and China. The degree of the export rivalry or competition between these countries in the Japanese market is examined in two stages. First, using the GTAP (Global Trade Analysis Project Model) to simulate the liberalization impact on the export of these countries in the Japanese market, as well as the Japanese export to these countries. Second, by using the conventional shift-share methodology in order to sense the degree of competition. Findings from this empirical work show that in general China will benefit more than ASEAN-5 countries from the WTO and APEC trade liberalization, especially in its export of textile and resource based manufactures to the Japanese market. Contrarily, ASEAN-5 countries will somewhat suffer some disadvantage on its export to Japan. However, Indonesia and the Phillipines can still rely on its export of resource based manufactures, while Malaysia would still maintain its advantage on its high technology and capital intensive products, Singapore on its service sector, and Thailand on is agricultural manufactures. Japan would benefit most on its bilateral trade with China. Simulations show that there will be an increase of intra-trading, especially in the textile market with China, and agricultural manufactures market with Thailand.Keywords : Trade liberalization, export competitiveness, GTAP, specialization